1000 icons, symbols + pictograms : visual communications for every language : 1,000 works - Blackcoffee (Firm) (Gloucester, MA : Rockport, 2006)
"This new collection of 1,000 icons, symbols, and pictograms from all types of industries, used for all types of communication, is an invaluable resource for any designer." "Pictorial symbols are in some respects superior to words as a form of communication because they can be understood by people from around the world. Because of this, such symbols often supplant words like "Men," "Women," "Hotel," "Taxi," and "Camping." Additionally, with the digital age changing our verbal vernacular, we are seeing symbols replace the written word in navigation menus on the Web, cell phones, and the numerous remotes that inundate our lives. This new visual language is immediate, global, and expected, so designers are continually charged with creating and incorporating these types of visual clues in all areas of design. This collection will inspire designers to think beyond the expected, and open their eyes to new ways of communicating."--BOOK JACKET.
Includes index.
Keywords: Signs and symbols -- Pictorial works; Visual communication -- Pictorial works